Neuromyths in Education and Development: A Comprehensive Approach - Papatzikis, Efthymios (European Scientific Journal, ESJ, 2017)
A lot of people imagine neuroscience, and its neuroimaging techniques, as the holly grail of information as far as the capacities of the brain and its developmental path is concerned. Therefore, not long ago, there was a rage for â€œbrain-based learningâ€. It purported to use neuroscience to design activities that were more amenable to the brainâ€™s structure and behavior, or that helped to integrate the work of the two hemispheres. For several decades thereafter, myths about the brain â€” neuromyths â€” have persisted in all cognitive, social and environmental levels, often being used to justify ineffective approaches to teaching, learning and reacting to various stimuli found in our everyday life. Many of these myths are biased distortions of scientific fact. Cultural conditions, such as differences in terminology and language, as well as general miscommunication have all contributed to a â€˜gapâ€™ of knowledge that has largely shielded these distortions from scrutiny, while further â€˜harmâ€™ typical and atypical development in both the educational and the professional contexts. The aim of the specific paper is to present the nature and substance of neuromyths, after explaining five major of them and providing a way to act against their creation or to avoid them when met.